Unraveling the relationship between nutritional status, cognitive function, and school performance among school-aged children in Taabo, Côte d'Ivoire: a school-based observational study - Tia, Achil; Hauser, Jonas; Konan, Amoin G.; Ciclet, Olivier; Grzywinski, Yohan; Mainardi, Fabio; Visconti, Gioele; Frézal, Adrien; Nindjin, Charlemagne (Frontiers in Nutrition, 2025)
BackgroundNutritional deficiencies are one of the main factors that affect cognitive development. In Côte d'Ivoire, although nutritional deficiencies have been reported among schoolchildren, their association with cognitive function or academic performance remains unexplored.ObjectiveThe objective of this study was to investigate the relationship between nutritional status, cognition, and school performance in school-aged children from Taabo, Côte d'Ivoire.MethodsA sample of 252 schoolchildren (6–12 years) was recruited. Nutrient biomarkers were measured in blood samples, cognition (fluid intelligence) was assessed using the Raven's Colored Progressive Matrices (RCPM), and school performance was quantified based on academic results in mathematics and literature.ResultsOverall scores were 15.4 ± 4.4 for the RCPM, 6.0 ± 2.4 for mathematics, and 5.4 ± 1.8 for literature (out of a maximum of 36, 10, and 10, respectively). Most of the children had normal nutritional status, but all had inadequate plasma levels of iron, folate, thiamine, and vitamin B12. Significant correlations (p < 0.05) were found between biomarkers of iron, folate, tryptophan, calcium, potassium, and omega-3 fatty acids with cognition or school performance. In contrast, no associations were found with zinc, iodine, riboflavin, vitamin B12, or vitamin D. After adjusting for sociodemographic factors in regression models, calcium was identified as a predictor of cognitive skills (R2 = 0.3, p = 0.020; 95% CI: 8.2 × 10−6−9.3 × 105) and folate as a predictor of performance in both mathematics (R2 = 0.1, p = 0.006; 95% CI: 0.1–0.3) and literature (R2 = 0.1, p = 0.005; 95% CI: 0.1–0.2).ConclusionThis study found high rates of B vitamins and iron deficiencies in Ivorian school-aged children. Iron, folate, tryptophan, calcium, potassium, and omega-3 fatty acid biomarkers showed promising correlations with cognition and academic performance. Further research aimed at investigating such relationships is needed.